Postoperative chemotherapy improves survival in patients with resected high‐risk Stage II colorectal cancer: results of a systematic review and meta‐analysis. (27th February 2020) - Simillis, C.; Singh, H. K. S. I.; Afxentiou, T.; Mills, S.; Warren, O. J.; Smith, J. J.; Riddle, P.; Adamina, M.; Cunningham, D.; Tekkis, P. P.
Abstract: Aim: The aim was to assess the benefit of adjuvant chemotherapy in high‐risk Stage II colorectal cancer. Method: A systematic literature review and meta‐analysis was performed comparing survival in patients with resected Stage II colorectal cancer and high‐risk features having postoperative chemotherapy vs no chemotherapy. Results: Of 1031 articles screened, 29 were included, reporting on 183 749 participants. Adjuvant chemotherapy significantly improved overall survival [hazard ratio (HR) 0.61, P < 0.0001], disease‐specific survival (HR = 0.73, P = 0.05) and disease‐free survival (HR = 0.59, P < 0.0001) compared to no chemotherapy. Adjuvant chemotherapy significantly increased 5‐year overall survival (OR = 0.53, P = 0.0008) and 5‐year disease‐free survival (OR = 0.50, P = 0.001). Overall survival and disease‐free survival remained significantly prolonged during subgroup analysis of studies published from 2015 onwards (HR = 0.60, P < 0.0001; HR = 0.65, P = 0.0001; respectively), in patients with two or more high‐risk features (HR = 0.59, P = 0.0001; HR = 0.70, P = 0.03; respectively) and in colon cancer (HR = 0.61, P < 0.0001; HR = 0.51, P = 0.0001; respectively). Overall survival, disease‐specific survival and disease‐free survival during subgroup analysis of individual high‐risk features were T4 tumour (HR = 0.58, P < 0.0001; HR = 0.50, P = 0.003; HR = 0.75, P = 0.05), < 12 lymph nodes harvested (HR = 0.67, P = 0.0002; HR = 0.80, P = 0.17; HR = 0.72, P = 0.02), poor differentiation (HR = 0.84, P = 0.35; HR = 0.85, P = 0.23; HR = 0.61, P = 0.41), lymphovascular or perineural invasion (HR = 0.55, P = 0.05; HR = 0.59, P = 0.11; HR = 0.76, P = 0.05) and emergency surgery (HR = 0.60, P = 0.02; HR = 0.68, P = 0.19). Conclusion: Adjuvant chemotherapy in high‐risk Stage II colorectal cancer results in a modest survival improvement and should be considered on an individual patient basis. Due to potential heterogeneity and selection bias of the included studies, and lack of separate rectal cancer data, further large randomized trials with predefined inclusion criteria and standardized chemotherapy regimens are required.